Fluid biomarkers in stroke: From animal models to clinical care. (15th July 2022) - Dias, Alexandre; Silva, Lénia; Moura, João; Gabriel, Denis; Maia, Luis F.
Abstract : Stroke is a leading cause of death and disability worldwide. Stroke prevention, early diagnosis, and efficient acute treatment are priorities to successfully impact stroke death and disability. Fluid biomarkers may improve stroke differential diagnostic, patient stratification for acute treatment, and post‐stroke individualized rehabilitation. In the present work, we characterized the use of stroke animal models in fluid biomarker research through a systematic review of PubMed and Scopus databases, followed by a literature review on the translation to the human stroke care setting and future perspectives in the field. We found increasing numbers of publications but with limited translation to the clinic. Animal studies are very heterogeneous, do not account for several human features present in stroke, and, importantly, only a minority of such studies used human cohorts to validate biomarker findings. Clinical studies have found appealing candidates, both protein and circulating nucleic acids, to contribute to a more personalized stroke care pathway. Still, brain tissue complexity and the fact that different brain pathologies share lesion biomarkers make this task challenging due to biomarker low specificity. Moreover, the study design and lack of validation cohorts may have precluded a formal integration of biomarkers in different steps of stroke diagnosis and treatment. To overcome such issues, recent pivotal studies on biomarker dynamics in individual patients are providing added value to diagnosis and anticipating patients' early prognosis. Presently, the most consistent protein biomarkers for stroke diagnosis and short‐ and long‐term prognosis are associated with tissue damage at neuronal (TAU), axonal (NFL), or astroglial (GFAP and S100β) levels. Most promising nucleic acids are microRNAs (miR), due to their stability in plasma and ease of access. Still, clinical validation and standardized quantitation place them a step behind compared protein as stroke biomarkers. Ultimately, the definition of clinically relevant biomarker panels and optimization of fast and sensitive biomarker measurements in the blood, together with their combination with clinical and neuroimaging data, will pave the way toward personalized stroke care.